Mud Volcanoes, Geodynamics and Seismicity Proceedings of the NATO Advanced Research Workshop on Mud Volcanism, Geodynamics and Seismicity, Baku, Azerbaijan, from 20 to 22 May 2003 - Martinelli, Giovanni; Panahi, Behrouz; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2005)
1. PURPOSE OF PRESENT BOOK During the period May 19-26, 2003 the NATO Advanced Research Workshop (ARW) “Mud volcanism, Geodynamics and Seismicity” was held in Baku. Participants coming from USA, Germany, France, Italy, Portugal, Russian Federation, Ukraine, Romania, Georgia, UK, Israel, Azerbaijan, Tunisia have discussed about different geodynamic features of mud volcanism and participated to field trips oriented to a better knowledge of mud volcanic features. The Meeting focused on many features of mud volcanism occurrence and related geodynamic topics. The purpose of present book is to collect contributions discussed during the Meeting and to fill a marked editorial gap on mud volcanism. Mud volcanism was to date described by local monographies or by articles published by scientific journals. In particular no books were published on topics able to highlight the link among mud volcanism, geodynamics and seismicity. Mud volcano of Nirano (Northern Italy). Engraving from Stoppani A. (1871), Corso di Geologia, Milan, Bernardoni G. and Brigola G. Publishers. 2. WHY MUD VOLCANOES ARE GEOLOGICALLY IMPORTANT ? Mud volcanoes have attracted the attention of earth scientists for many years. Due to their importance in hydrocarbon research, a consistent progress in the knowledge of mud volcanism took place in the past twenty years. Mud extrusion is a well-known phenomenon occurring in geological environments where fluid-rich, fine grained sediments ascend within a lithologic succession due to their buoyancy.
Mud Volcanic Geology -- New Seismic Neogene Clay Diapirs and Hydrocarbon Implications in the North-Eastern African Margin of Tunisia -- Seismic Signature of Gas Hydrate and Mud Volcanoes of the South African Continental Margin -- Global Distribution of Mud Volcanoes and Their Significance in Petroleum Exploration as a Source of Methane in the Atmosphere and Hydrosphere and as a Geohazard -- Styles and Productivity of Mud Diapirism along the Middle American Margin -- Styles and Productivity of Mud Diapirism along the Middle American Margin -- Geodynamic Implications of Mud Volcanism -- Mud Volcanoes and Seismicity in Romania -- Mud Volcanism, Geodynamics and Seismicity of Azerbaijan and the Caspian Sea Region -- Seismic Hazard and Mud Volcanism -- Mud Volcanic Manifestations in the Maximum Shaking Areas of Strong Earthquakes -- The Areas of Mud Volcanism in the South Caspian and Black Sea: Seismicity and New Technology for Seismic Risk Estimation -- Recent Seismic Activity in Albania and its Features -- Assessment of Seismic Hazard in Areas of Mud Volcano Location on the Basis of Geophysical Data -- Greenhouse Effects of Mud Volcanism -- Methane Emission from Mud Volcanoes -- Gas Emissions from Mud Volcanoes -- Monitoring Techniques of Mud Volcanism -- Mud Volcanoes of Pakistan — an Overview -- Monitoring of Deformation Processes by Means of Electric Field Observation -- Mud Volcano: Methods, Apparatus — Fundamental and Applied Aspects of Research -- Mud Volcano Monitoring and Seismic Events -- Insar Analysis of the Absheron Peninsula and Nearby Areas, Azerbaijan -- Geochemical Features of Mud Volcanoes -- Geochemical Model of Mud Volcanoes from Reviewed Worldwide Data -- Biosensor Control of Acute Total Toxicity of Water and Soil Polluted by Polycyclic Aromatic Hydrocarbons -- Yeh,^Gau-Hua -- Physical Models of Mud Volcanoes -- Mud Volcanoes as Natural Strainmeters -- Mud Volcano Model Resulting from Geophysical and Geochemical Research -- Physical Properties of Muds Extruded from Mud Volcanoes: Implications for Episodicity of Eruptions and Relationship to Seismicity.
Keywords: Earth sciences; Geochemistry; Geophysics; Hydrogeology; Mineral resources; Earth Sciences, general; Geochemistry; Geophysics/Geodesy.; Hydrogeology; Mineral Resources